IMPROVING THE SYSTEM OF CONTROL AND SUPERVISION OF CUSTOMS IN THE REGION - A. S. Nikitina; D. A. Nuzhina (Вестник университета)
Customs regulation as a type of management activity of customs authorities is one of the key elements of the customs system and the economy of the state. The control and supervision activities of the customs authorities should be carried out on a systematic basis, and the key goal of this type of work is to improve customs regulation for increasing the efficiency of the customs system and optimize the activities of customs authorities. The problems and ways to improve the system of control and supervision in the field of customs in the region (on the example of the Ural Customs Administration) have been analyzed in the article. The main practical research methods are the analysis of statistical data and regulatory sources, a sociological study using the expert survey method (n = 13). As a result, a systematization of problematic aspects of the control and supervision in the field of customs has been proposed; a system of measures has been developed aimed at improving the quality of control and supervision in the field of customs.